Inpatient Management of Pain Episodes in Children with Sickle Cell Disease: A Review - Zhour Barnawi; Ronay Thomas; Radhika Peddinti; Nabil Abou Baker (MDPI AG, 2024)
Sickle cell disease (SCD) is the most common hemoglobinopathy in the world. Sickle cell vaso-occlusive episodes (VOEs) are very painful acute events and the most common complication as well as reason for hospitalization. SCD pain is best evaluated holistically with a pain functional assessment to aid in focusing pain management on reducing pain in addition to improving function. Patients with SCD have long endured structural racism and negative implicit bias surrounding the management of pain. Thus, it is important to approach the management of inpatient pain systematically with the use of multi-modal medications and nonpharmacologic treatments. Furthermore, equitable pain management care can be better achieved with standardized pain plans for an entire system and individualized pain plans for patients who fall outside the scope of the standardized pain plans. In this article, we discuss the best practices to manage SCD VOEs during an inpatient hospitalization.